Co-location and Coopetition as the Sources of Slow (City) Tourism:Case Rovaniemi - Haapakoski, Anna-Emilia; Tikkanen, Juulia; Rusko, Rauno (Emerald Publishing, 2024)
This chapter considers the role and features of co-location and coopetition in the framework of slow (city) tourism using the city of Rovaniemi as a case study example. Rovaniemi, as a tourism destination, contains three main service agglomerations: Santa Claus Village near the Arctic Circle and the Official Airport of Santa Claus, the City centre with three shopping centres and Ounasvaara sports centre, which together constitute, based on co-location, and intentional and unintentional coopetition, one attractive destination providing possibilities for tourism due to several services and activities of the area. Slow tourism is an important emerging tendency to enable the possibility of diminishing overtourism and rethinking the value(s) of local development. Through applying the concepts of slow into tourism city planning, the empowerment and well-being of local communities in increasingly popular global destinations like Rovaniemi are emphasised. Rovaniemi, the city now known as the hometown of Santa Claus, has multilevel coopetitive activities to create year-round locally engaging tourism in order to restrain the development of seasonal overtourism.